The politics of industrial relations. Labor unions in Spain - Hamann, Kerstin (London, 2012)
"As unions in most other industrialized democracies continue to decline, unions in Spain have been able to regain and maintain strength despite unfavorable institutional, political, and economic conditions. The Politics of Industrial Relations provides a comprehensive analysis of Spanish unions from the Franco dictatorship until the present. It builds on industrial relations, comparative politics, and political economy literature to investigate the trajectory of Spanish unions. The book analyzes unions as political actors, that is, their interaction and involvement with governments, political parties, and nationwide policy-making processes to explain why Spanish unions appear in some ways as atypical in West European comparison. The development of Spanish unions and industrial relations is framed in a historical-institutionalist approach while also taking into account globalization and Europeanization processes. Using the case of the Spanish transition to democracy, the book demonstrates that the historical sequencing of institutional reforms in the political and industrial relations arenas holds significant and long-lasting consequences for the nature of unions and labor relations. The book concludes that by understanding unions as political actors, the history of Spanish unionism and industrial relations institutions is more easily accommodated than looking at unions as industrial actors alone."